Evaluación de la Harina de Achiote (bixa o rellana l) como pigmentante en el vitelo de Huevo de la Gallinas Lohmann Brown- Classic de la Avicola Marlito Parroquia Eloy Afaro. - Moreno Moreno, Karina Priscila (2018)
The following research evaluated the achiote flour (Bixa Orellana 1) as a pigmenting in the egg yolk of Lohmann Brown- classic hens of Marlito poultry sector in Eloy Alfaro parish. The research was developed in “Marlito poultry farming” located in Zumbalica neighborhood, Eloy Alfaro parish canton Latacunga. The research carried out with 200 chickens of 34 weeks of age distributed in 2 treatments (0% and 5% achiote flour). 100 birds for each treatment with 13 repetitions each one for a period of 93 days. Each week the weight of the chickens was recorded, weight of the egg, weight of the yolk, weight of white, weight of the skin, height of the yolk and degree of pigmentation of the yolk. T-student was used to analyze the research. The data collection showed that using 5% of achiote flour inside of the additives in the daily diet of the chickens, does not significantly affect the organoleptic features of the egg (P>005). The egg yolk pigmentation increased significantly (P<0,05) in the first stage, week 34 to 38 the yolk has a pigmentation degree of 12. Second week stage, week 39 to 42 the yolk has a pigmentation degree of 13. And the third stage, week 43 to 46 has a pigmentation degree of 14 according to the Roche color range. Regarding the benefit / cost, achiote flour application has a profit of 0.32 USD. To conclude, achiote flour can be used without causing detrimental effects on the performance of laying hens.